Building Safety Regulations in The Construction of Housing Projects - Nur Hidayah Rais,; Nurul Asra Abd Rahman,; Zarina Alias,; Zainab Mohmad Zainordin,; Suryani Ahmad, (Online Journal for TVET Practitioners, 2025)
Building safety regulation was become the main issue in the construction industry because of the increased rate of death and injury among workers in the workplace. This research aims to identify effective safety compliance towards the Occupational Safety and Health (OSHA) by developers and consultants to minimise the risk in the construction of housing projects. The objective is to explore the importance of building safety regulations in the construction of housing projects. The interview session has been conducted among developers and consultants in the construction industry, which are currently involved in construction of housing projects. All the data collected were examined utilising theme analytic techniques. The study has identified that there were six (6) themes of impacts with non-compliance with safety regulations, (1) Financial penalties, (2) Loss of productivity, (3) Damage to the end loss of materials, plant, and equipment, (4) Time loss, (5) Endangering lives and (6) Industry disqualification. This findings will be able to determine the effects of non-compliance with safety regulation requirements in the construction of housing projects.